PENYULUHAN TENTANG PENTINGNYA PENERAPAN INTERVENSI TRIK 20-20-20 DALAM PENCEGAHAN COMPUTER VISION SYNDROME PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT - Fithri Handayani Lubis; Bunga Mari Sembiring; Hengki Frengki Manulang; Herawati Bukit; kristin Natalia (INSTITUT KESEHATAN DELI HUSADA, 2022)
It is worried that the increasing use of gadgets during the Covid-19 pandemic will pose a health threat, especially for students studying online. One of the things that often occurs due to excessive use of tools called computer vision syndrome (CVS), is one of the eye problems that causes serious eye disorders. This CVS refers to prolonged close work that a person experiences during or in connection with computer use. The most common visual symptoms reported by computer users are double vision and blurred vision at near, far and medium distances. Common causes of blurred computer use include refractive errors, accommodation disorders (impaired focusing system of the eye), presbyopia (decreased ability to focus at longer distances with age), and binocular vision disorders (impaired binocular alignment). Musculoskeletal symptoms commonly experienced by computer users include neck, back, shoulder, wrist, and finger pain. Computer posture errors are an important factor associated with musculoskeletal symptoms. The American Optometric Association recommends performing the 20-20-20 trick every 20 minutes, focusing the eyes at a distance of 20 feet (6 meters) for the remaining 20 seconds, this trick is especially helpful for the following. Solve the problem. Symptoms of CVS experienced by computer users.This activity was held at the Auditorium of the DELI HUSADA Institute of Health in September 2021. The entire academic community at the Faculty of Public Health who attended the meeting was very enthusiastic. The counseling activity has been able to increase the knowledge of participants at the DELI HUSADA Faculty of Public Health regarding the importance of implementing the 20-20-20 Trick Intervention for the prevention of Computer Vision Syndrome.